Identifying the 'savanna' signature in lacustrine sediments in northern Australia. (1st January 2019) - Bird, Michael I.; Brand, Michael; Diefendorf, Aaron F.; Haig, Jordahna L.; Hutley, Lindsay B.; Levchenko, Vladimir; Ridd, Peter V.; Rowe, Cassandra; Whinney, James; Wurster, Christopher M.; Zwart, Costijn
Abstract: This study reports palynological and geochemical results for modern and ancient sediments from 19 lakes on a rainfall gradient (784–1880 mm), across a range of savannas in Northern Australia. All proxies varied significantly across the range of sites examined, providing a robust envelope of values that can reliably be employed to identify a savanna signature in the sedimentary record. While the results indicate it is possible to identify a savanna, we found only three statistically significant relationships between any proxy measured in surface sediments and the major climate driver of savanna vegetation composition (rainfall amount). This is because edaphic factors play a dominant role in determining vegetation composition and also potentially because of the impact of land use change. Measures of fire determined by charcoal counting were positively correlated with geochemical measures of pyrogenic carbon abundance, suggesting both record a similar signal. While measures of fire incidence were not correlated with rainfall, there was a significant positive correlation between charcoal abundance and number of fires early in the dry season, suggesting that charcoal abundance is controlled more by the number/timing of fires than climate. There was also a significant correlation between the δ 13 C-value of pyrogenic carbon and tree:grass ratio derived from palynological indicators, indicating that the δ 13 C-value of PyC is a reliable indicator of savanna 'woodiness'. Comparison of the carbon isotope composition of total organic carbon, PyC and n -alkanes between modern and Holocene sediments suggest that the savannas of the region have remained either similar in 'woodiness' or have thickened over the last millennia.